Characteristics and leaching behavior of MSWI fly ash in novel solidification/stabilization binders. (15th July 2021) - Fan, Chengcheng; Wang, Baomin; Qi, Yi; Liu, Ze
Highlights: M–S–H binder is a novel candidate used for MSWI fly ash immobilization. Low alkalinity of M–S–H binder was beneficial for heavy metals encapsulation. Immobilization mechanism of M–S–H solidified body was fully explored. Abstract: Municipal solid waste incineration (MSWI) fly ash has become a challenge for waste management because it is rich in heavy metals and its output is increasing sharply year by year. A novel binder system for MSWI fly ash solidification/stabilization was produced by blending MgO and silica fume in this work. And several tests including compressive strength, toxicity leaching behavior, hydration products, pore structure and micromorphology of MgO-SiO2 -H2 O (M–S–H) binders without and with MSWI fly ash were conducted. Results showed that the compressive strength of MSWI fly ash-blended samples varied from 1.8 MPa to 29.3 MPa, and the maximum leaching concentration of Pb, Zn and Cd were 0.052 mg/L, 1.02 mg/L, 0.098 mg/L, which all met the national standard limitation on the landfill site. Besides, M–S–H binders could buffer against the harsh acid environment at a certain degree, which would provide a proper low alkalinity environment for immobilization of heavy metals such as Pb, Zn and Cd in MSWI fly ash. Meanwhile, the microstructure and morphology characteristics analysis results demonstrated that the favorable ion exchange and high specific surface area of hydration product contributed much to the excellent immobilization and adsorption characteristics on heavy metals, so it can be deduced that M–S–H binders mainly fixed the heavy metals by the physical encapsulation and chemical bonding. Overall, this work demonstrated that the application potential of M–S–H as immobilization binders in the field of sustainable construction materials and hazardous waste management, and providing a new way for the development and utilization of magnesium resources.